Pendampingan Majelis Bimbingan Dakwah Di MAN 2 Cirebon - Aghuts Muhaimin; Khaerun Khaerun; Abdul Kohar; Susi Susi; Rokim Rokim; Safrudin Safrudin (Etos : Jurnal Pengabdian Masyarakat, 2020)
The management of the message preaching guidance council is judged by some to be no longer able to make a real contribution to the community to carry out social transformation in fact, what has happened is the opposite has created a wide gulf between the community and, due to the closed relationship between the parties and the community. as if it has formed an "exclusive community" that no longer wants to be in contact with the surrounding community. education in today's global era, is more varied in offering educational services to the community, with criteria that are in accordance with the needs of the community, especially in terms of da'wah, because the da'wah guidance assembly is the heart of a madrasa that has a religious program. Abstrak Manajemen majelis bimbingan dakwah pesan dinilai oleh sebagian orang sudah tidak mampu lagi memberikan kontribusi nyata bagi masyarakat untuk melakukan transformasi sosial bahkan, yang terjadi adalah kebalikannya telah tercipta sebuah jurang pemisah yang lebar antara masyarakat dan, dikarenakan hubungan yang tertutup oleh pihak dengan masyarakat. seolah-olah telah membentuk "komunitas eksklusif" yang tidak mau lagi bersentuhan dengan masyarakat sekitarnya. pendidikan pada era global sekarang ini, lebih berfariatif dalam menawarkan pelayanan pendidikan terhadap masyarakat, dengan kriteria-kriteria yang sesuai dengan kebutuhan masyarakat, khususnya dalam hal dakwah, karena majelis bimbingan dakwah merupakan jantung dari sebuah Madrasah yang mempunyai program keagamaan